APPLICATION OF MULTI CRITERIA DECISION MAKING METHODS TO LEACHING PROCESS OF COPPER FROM MALACHITE ORE - Kurşuncu, Bilal; Yaraş, Ali; Arslanoğlu, Hasan (Yıldız Teknik Üniversitesi, 2018)
This study concerns with optimization of the leaching conditions of copper from malachite ore in the presence ammonium nitrate solution. In order to select the effective parameter from available dissolution process, all experiments were performed using L25 orthogonal experimental design by Taguchi method and the temperature was found as a more effective parameter. Then multi-criteria decision making (MCDM) method was applied to experimental results and it was found that the process is in concordance with MCDM values. Based on the results, the highest copper extraction value (99.4%) was reached under optimum leaching conditions are as follows: time, 60 min; temperature, 75oC; stirring speed, 450 rpm; concentration of leaching reagent, 4 mol/L and solid/liquid ratio, 8 g/mL. In conclusion, Taguchi and MCDM method can be used effectively for optimization of various hydrometallurgical processes.
Keywords: Engineering; Mühendislik